Effect of PGPR as Biofertilizer on Growth and Yield of Paddy (ADT 36) - M, Manivannan. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Plant growth promoting rhizobacteria (PGPR) are naturally occurring soil bacteria that aggressively colonize plant roots and benefits plants by providing growth promotion. Inoculations of crop plants with certain strains of PGPR at an early stage of development improve biomass production through direct effects on root and shoot growth. The use of PGPR is steadily increasing in agriculture and offers an attractive way to replace chemical fertilizers and pesticides. Here, we have used certain PGPR traits from the rhizosphere soil of rice and tested for its biofertilizer potential as applied in three ways via., seed treatment, seed treatment along with soil application and soil application alone in order to growth and yield enhancement of rice variety ADT 36. Among the three different PGPR traits namely., Azospirillum, Azotobacter and Pseudomonas, Azospirillum showed the best results by means of growth promotion in rice for seedling emergence, increase of shoot length, root length, dry matter production, chlorophyll content and yield parameters like increase of thousand grain weight, grain yield and straw yield. Besides PGPR biofertilizer activity, it helps to improve the soil fertility due to enhancement of the population of beneficial microbes such as bacteria, fungi and actinomycetes in soil. Since it is eco-friendly in nature, there has been much research interest in PGPR and there is now an increasing number of PGPR being commercialized for various crops. Finally concluding that PGPR namely Azospirillum has played an major role in enhancing the growth and yield of rice in our study.